Effect of Chemical Preservatives on the Shelf Life of Bread at Various Temperatures - Lohano, Dileep Kumar; Sheikh, Saghir Ahmed; Shahnawaz, Muhammad (Pakistan Journal of Nutrition, 2010)
The study was conducted to evaluate the “effect of chemical preservatives on the shelf life of bread at various temperatures” at the Institute of Food Sciences and Technology, Sindh Agriculture University, Tandojam, in 2008. Two chemical preservatives i.e. calcium propionate (CP) and calcium lactate (CL) at (14±1), (22±1) and ambient temperature (32±2oC) were assessed for their effect on keeping quality of bread. The results conclude that effects of CP and CL at 14, 22 and (32±2oC) were equally significant at (p<0.01) for all chemical characteristics of bread. CP was more effective than CL such as moisture, protein, ash, TSS and carbohydrates were found 37.75 and 36, 9.24 and 8.75, 1.28 and 1.24, 5.10 and 4.71 and 47.75 and 47.01% with CP and CL respectively. Among the storage temperatures, 14oC demonstrate superior performance by increasing shelf life up to a maximum level i.e. 370 h/15.44 days followed by 22oC for 197 h/8.21 days and (32±2oC) for 123 h/5.12 days in decreasing order.